What kind of lifestyle can trigger early kidney function damage in adolescents? - Oktavia, Fadila; Wahyuningtyas, Eka Sakti; Masithoh, Robiul Fitri (Innovation in Health for Society, 2026)
Kidney function damage in adolescents can be influenced by lifestyle behaviors and family risk factors. However, limited studies in Indonesia assessed the risk factor of kidney injury among adolescents. Therefore, this study aims to describe the lifestyles that potentially trigger early kidney function damage among junior high school students. The research employed a descriptive observational design with a quantitative approach. The sample consisted of 60 students selected using a purposive sampling technique. Data were collected via questionnaires covering eating and drinking patterns, physical activity, smoking habits, family medical history, and mild symptoms of kidney disorders, which were then analyzed using descriptive statistics.  The results showed that while most respondents were in the "good" category overall, several risk factors were still identified. Specifically, 51.7% of respondents did not meet daily water intake requirements, and 56.7% frequently consumed salty foods. Physical activity was dominated by low to moderate categories, with 55.0% not exercising routinely and 71.7% failing to meet the minimum physical activity requirement of 150 minutes per week. The majority of respondents were non-smokers, though a small percentage engaged in light smoking. A family history of hypertension was found in 46.7% of respondents, and diabetes in 13.3%. Furthermore, some respondents reported mild symptoms such as changes in urination, itching, fatigue, and concentration difficulties. The study concludes that there is a combination of unhealthy lifestyle behaviors, family risk factors, and early symptoms that potentially trigger kidney function disorders in adolescents. Therefore, promotive and preventive efforts through health education and the cultivation of healthy living habits starting from school age are necessary to preserve kidney function in the future. Keywords: Acute kidney injury, eating and drinking patterns, medical history, physical activity, smoking habits, symptoms of kidney failure